2011
DOI: 10.1111/j.1541-0072.2011.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Credibility, Disagreement, and Error Costs in 17 Biotechnology Policy Subsystems

Abstract: One of the original objectives of the advocacy coalition framework (ACF) was to shed light on the role of science in policymaking. The ACF depicts subsystem scientists as political actors just like any other. Unfortunately, science has never become a major theme of research within the framework and, as a consequence, its role in policymaking remains under‐theorized, leaving ample room for interpretation. This article seeks to explore the validity of three propositions about the role of science in policy. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
(39 reference statements)
1
47
0
Order By: Relevance
“…An important stream of public policy research asks how experts associate with different coalitions of actors in policy-making processes (e.g., Weible et al 2010;Sabatier and Zafonte 1995;Montpetit 2011;Weible et al 2011;Weiss 1979). The model of expert thinking provided here hints at answers.…”
Section: Resultsmentioning
confidence: 98%
“…An important stream of public policy research asks how experts associate with different coalitions of actors in policy-making processes (e.g., Weible et al 2010;Sabatier and Zafonte 1995;Montpetit 2011;Weible et al 2011;Weiss 1979). The model of expert thinking provided here hints at answers.…”
Section: Resultsmentioning
confidence: 98%
“…In policy domains where scientific knowledge is important, such as biotechnology, university scientists also have shifting positions. They must be sensitive to the rapid expansion of scientific knowledge, to constant questioning and to complex science/politics overlaps (Gutie´rrez 2010;Montpetit 2011). In contrast, career civil servants, who have been socialised to the importance of detachment, have successfully accomplished their work when they have provided dispassionate advice, sensitive only to bureaucratic experiences and analysis.…”
Section: Detachment and The Attitudes Of Civil Servantsmentioning
confidence: 92%
“…In our absent self-awareness of this decisive political component, we-scientists, policy-makers and the public-run the risk of naively trusting science and technology elites, who are clearly not aligned themselves in belief and conviction [2]. In short, there is no credible basis for assuming that scientists invariably consider the best interests of society when engaging in the scientific enterprise.…”
mentioning
confidence: 97%
“…For instance, an analysis of scientific expertise about the risks and benefits of biotechnology applications in human genetics and in the agri-food domain in 17 subsystems in Europe and North America found that scientists are less likely to agree among themselves about the risks and benefits of biotechnology applications than other policy actors, and are motivated by strongly held beliefs and convictions [2].…”
mentioning
confidence: 99%